Use of Antimicrobials without Prescription - Amna Noor ,Seemi Gull , Shahzad Manzoor (Journal of Rawalpindi Medical College, 2014)
Background: To evaluate the prevalence of antibiotic self medication and to assess the knowledge and reasons for the misuse of antibiotics. Methods: In this cross sectional study 187 non medical employees of Rawalpindi Medical College were enrolled. Questionnaire was designed to assess reported purchase, name and use of antibiotic without prescription. Results: The most commonly named antibiotic purchased and used without a prescription was Co-amoxiclav(37%) followed by Amoxicillin(22%). There was a significant difference between the educational level and antibiotics at the probability level of <0.05. Sore throat (27%) was the common condition for the use of antibiotics followed by fever and diarrhea (14%). Ten females out of 43 (23%) were the mother of 1-2 children, they commonly used Ceftriaxone (5%) for the cure of their children. Employees belonging to level 1 were illiterate; they never used antibiotics without prescription. Only 30% correctly named an antibiotic as the medicine purchased. Among the respondents who purchased an antibiotic without a prescription, 70% used medicine for inadequate duration (< 5days) or at wrong dosing intervals. Conclusion: Prevalence of self medication with antimicrobials is high in educated employees, despite majority being aware of its harmful effects.